Further Validation of a Dutch Translation of the Sussex Oxford Compassion for the Self Scale in Samples of Crisis Line Volunteers, Military Personnel and Nursing Students - de Krijger, Eva; Willems, Renate; ten Klooster, Peter; Bakker, Ellen; Miedema, Harald; Drossaert, Constance; Bohlmeijer, Ernst (Frontiers in Psychology, 2022)
Self-compassion is considered an important, transdiagnostic factor for mental health. The Sussex Oxford Compassion for the Self Scale (SOCS-S) is a recently developed comprehensive measure of self-compassion, that was found to have promising psychometric properties among health care staff and university students in the initial validation study. The aim of this study is the further psychometric evaluation of the SOCS-S in different populations and settings. The SOCS-S was administered in three different Dutch samples (crisis line volunteers [n = 560], military personnel [n = 244] and nursing students [n = 255]). The results confirm the five-factor structure of the SOCS-S and its reliability and concurrent and construct validity across the samples. Measurement invariance was demonstrated for gender but not for different age groups and professions. Finally, the SOCS-S was found to explain additional variance in mental health in comparison to a widely used self-compassion measure.